Clinical Evaluation and Management of Urolithiasis in Dogs - Karir, Shree Ram; Anita; Bharia, Alka; Pandey, Nupur; Kumar, Pradeep (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Urolithiasis, characterized by the formation of urinary tract calculi, is a common and potentially serious condition in dogs. It may result in  partial or complete urinary obstruction and often recurs if not properly managed. The condition has a multifactorial etiology, involving  diet, infection, breed predisposition and urinary pH. This study was focused on diagnostic imaging, surgical intervention outcomes and  prevention of post-treatment recurrence of urolithiasis in ten dogs. Clinical signs, diagnostic imaging (radiography and ultrasonography),  stone composition, surgical and medical management and follow-up were analysed. Stones were identified chemically and post-treatment  protocols were followed. The most frequent stone type was struvite (5 cases), followed by calcium oxalate (3 cases) and urate (2 cases).  Surgical intervention was necessary in 8 dogs. Two urate cases were managed with diet modification alone. Most dogs recovered fully,  with recurrence in one case. Imaging was instrumental in identifying radiolucent and radiopaque calculi. Canine urolithiasis requires  comprehensive diagnostic evaluation and individualized therapy. Combining surgery, diet modification and long-term monitoring offer  the best outcomes. Accurate imaging and stone analysis are essential for preventing recurrence.
Keywords: Canine urolithiasis, Cystotomy, Calcium oxalate, Radiography, Struvite.